Konsep Pendidikan Akhlak Dalam Al-Qur’an: (Studi Pustaka Surah Luqman Perspektif Tafsir Klasik Dan Kontemporer) - Mizan, Mohamad Mizan Saroni; Rifqi Fauzi (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2024)
This study is grounded in the recognition that moral education constitutes a fundamental component in shaping human character, particularly when derived from the universal ethical principles of the Qur’an. Surah Luqman is selected as the primary textual source because it presents a comprehensive set of moral instructions, including the affirmation of monotheism, gratitude, worship, filial piety, social ethics, and self-discipline. The purpose of this research is to examine the concept of moral education in Surah Luqman through a comparative analysis of classical and contemporary exegetical works, thereby offering a deeper and more holistic understanding. This study employs a library research method, drawing from authoritative tafsir literature and supporting scholarly references. A thematic content analysis is used to identify the core educational values conveyed in the selected verses. The findings indicate that Luqman’s moral framework encompasses spiritual, ethical, and socio-behavioral dimensions that remain highly relevant to contemporary educational contexts. These values contribute significantly to the development of learners’ character.